Community perspectives of terrorism and the Nigerian government’s counterterrorism strategies: A systematic review - Ike, Tarela Juliet (Criminology & criminal justice, 2025)
Terrorism and insecurity pose significant global concern and Nigeria has been bedevilled by Boko Haram – a terrorist group deemed one of the deadliest terrorist groups in the world. While the Nigerian government have adopted concerted counterterrorism approaches to tackle terrorism, very limited success seems to have been achieved and the synthesis of community perspectives of government interventions appears lacking. This study makes an original and significant contribution by adopting a systematic review approach to synthesise existing studies on community perspective on the drivers of involvement in terrorism and on Nigerian government’s responses. Six databases were searched, and 21 studies met the review criteria. Informed by thematic analysis principles and the conceptual framework of synthesis, the study finds a sense of disconnect between the government approach to counterterrorism and community perspectives. The study recommends a context-specific community informed response to insecurity towards improving existing counterterrorism measures.